1998
DOI: 10.1161/01.cir.97.19.1907
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Geometry and Severe Left Ventricular Hypertrophy in Children and Adolescents With Essential Hypertension

Abstract: Background-Left ventricular (LV) hypertrophy has been established as an independent risk factor for cardiovascular disease in adults. Recent research has refined this relationship by determining a cutpoint of 51 g/m 2.7 for LV mass index indicative of increased risk and defining LV geometric patterns that are associated with increased risk. The purpose of this study was to evaluate severe LV hypertrophy and LV geometry in children and adolescents with essential hypertension. Methods and Results-A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
252
6
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(278 citation statements)
references
References 34 publications
6
252
6
14
Order By: Relevance
“…18 However, some studies failed to reveal an independent association of casual and/or ambulatory systolic/diastolic BP with LVMI or the presence of left ventricular hypertrophy, implying that factors such as the duration of hypertension or the characteristics of the study population (age, gender, presence of obesity or other comorbidities) may have an important role. [31][32][33] In the present study, LVM was significantly associated with systolic BP (mainly HBP and ABP and less so for CBP), nevertheless, LVMI was not significantly associated with systolic BP irrespective of the method used. This might be attributed, at least in part, to the fact that LVMI is an index corrected for body size, whereas BP (which in the pediatric population greatly varies according to age and body size) was used in the analyses unadjusted.…”
Section: Discussioncontrasting
confidence: 59%
“…18 However, some studies failed to reveal an independent association of casual and/or ambulatory systolic/diastolic BP with LVMI or the presence of left ventricular hypertrophy, implying that factors such as the duration of hypertension or the characteristics of the study population (age, gender, presence of obesity or other comorbidities) may have an important role. [31][32][33] In the present study, LVM was significantly associated with systolic BP (mainly HBP and ABP and less so for CBP), nevertheless, LVMI was not significantly associated with systolic BP irrespective of the method used. This might be attributed, at least in part, to the fact that LVMI is an index corrected for body size, whereas BP (which in the pediatric population greatly varies according to age and body size) was used in the analyses unadjusted.…”
Section: Discussioncontrasting
confidence: 59%
“…Among children and adolescents with primary HTN, 30-40% had a left ventricular mass index (LVMi) above the 95th percentile and 10-15% of them had severe left ventricular hypertrophy (LVH) defined as LVMi above 51g/height 2.7 (17)(18)(19). Renal damage is rarely observed in essential hypertensive children, but these subjects have greater albuminuria and excrete more N-acetyl glicosamine than their normotensive counterparts.…”
Section: Relative Cardiovascular and Renal Riskmentioning
confidence: 99%
“…Assessment of LVM and geometry remain a cornerstone when looking for end-organ damage in sustained pediatric HTN (17,103). The ratio of Doppler transmitral flow (E) and tissue Doppler derived early diastolic velocity (E´), reflecting diastolic function, independently predicts primary cardiac events in hypertensive adults (110).…”
Section: Heartmentioning
confidence: 99%
“…The arguments presented by Dr Daniels included an emphasis on the fact that obesity can amplify the severity of a pathological condition. 1 Indeed, by referring to his own clinical experience, 2 he showed that 'among children and adolescents with hypertension, increased BMI is associated with more severe increase in left ventricular mass index,' which may ultimately predict a large increase in the risk of cardiovascular end points in adulthood.…”
Section: Complications Of Obesity In Children and Adolescentsmentioning
confidence: 99%